PHENOTYPIC CHARACTERISTICS OF ACEH CATTLE ON DIFFERENT SEX AND AGE IN SMALLHOLDER FARMERS - Widi, T.S. Mastuti (2016)
This study was aimed to measure phenotypic characteristics of Aceh cattle on different sex and period of age in smallholder systems. Three areas (Muara Batu, Sawang and Nisam sub Districts in North Aceh District ) were used to collect data. Phenotypic characteristics were collected from 278 cattle (132 young and 146 adult cattle) with different sex and age. The result showed that male Aceh cattle were heavier and higher in young stage than female ones. In older stage, male Aceh cattle were also higher and had bigger girth of chest (GC) than female ones. However, length of the body (LB), depth of chest (DC) and height at hip (HH) of both male and female cattle were not significantly different on young and adult stages.